A MULTI-LEVEL ANALYSIS OF CURRICULUM ALIGNMENT IN INDONESIAN HIGHER EDUCATION: A CASE STUDY OF SELECTED DISCIPLINES AND THEIR IMPACT ON REGIONAL AND NATIONAL ECONOMIC DEVELOPMENT - Nana Suryapermana; Baktiar Nasution; Muhammad Syafri; Yorman; Al-Amin (Adisam Publisher, 2023)
This study comprehensively examines curriculum alignment within Indonesian higher education, focusing on the dynamic interplay of academic disciplines and regional influences. Utilizing a mixed-method approach, we explore the alignment of curricula in selected disciplines, including technical and social sciences, across diverse Jakarta, Surabaya, and Makassar regions. Our findings reveal significant variations in alignment, with technical disciplines demonstrating higher adaptability to industry demands while the humanities face distinct challenges. Moreover, regional disparities in curriculum alignment are identified, driven by industry concentration and geographical isolation. Notably, closely aligned curricula are linked to higher income growth, reduced unemployment, and enhanced industry competitiveness. The study emphasizes the pivotal role of stakeholder engagement in shaping curricula and fostering alignment. This research contributes valuable insights for policymakers, educators, and industry leaders seeking to enhance curriculum alignment and, in turn, bolster regional and national economic development in the context of Indonesian higher education.